Artificial Intelligence Ethics through the Lens of Maqāṣid al-Sharīʿah: Constructing a Normative Framework for Civilized Technology Governance - Maman Supardi; Hilmiy Hanif; Mursyid Rahman; Ahmad Fadhil Arham; Andi Muhammad Ali Amiruddin (Westscience Press, 2026)
The accelerating deployment of artificial intelligence (AI) across public and private life has outpaced the moral vocabularies available to evaluate it. Prevailing AI-ethics frameworks, articulated largely within Western traditions, converge on principles such as fairness, transparency, and accountability, yet remain thin on the spiritual and communal dimensions of moral judgement in Muslim societies. This study asks how maqāṣid al-sharīʿah, the higher objectives of Islamic law, may be operationalised as an evaluative instrument for AI governance rather than a declarative ideal. Employing qualitative library research, the study analyses primary Islamic sources alongside peer-reviewed scholarship from 2021 to 2026 through content analysis and philosophical-normative reasoning. The analysis maps four recurring problems (the erosion of privacy, algorithmic bias, opacity and diffuse accountability, and the attrition of human moral agency) and evaluates each against the five essential objectives (al-ḍarūriyyāt al-khams). The resulting framework translates every objective into governance criteria and correlates them with globally recognised AI principles, yielding an eleven-criterion instrument together with an ordering rationale for cases of value conflict. The study contributes an operational, value-based model that complements rather than displaces existing regulatory approaches, offering developers, regulators, and Shariah boards a design vocabulary for anticipating harm before deployment.